Lógicas institucionais e estruturas discursiva : um estudo do maternati - grupo de gestante e mães - Fernandes, Sara Picheth (2016)
The perspective of institutional logics allows to theorize and to evaluate the influence of institutions on individual and organizational behavior from the view that institutions are embedded in societal logics of superior orders. The institutional logics refer to beliefs, values, rules and historical patterns that have been socially constructed and that provide meaning to the social reality. Therefore, their study explains not only the homogeneity but also the heterogeneity in organizations, since it does not manifest itself in a deterministic way, but under a recursive bias, from interpretative processes, which are mediated through communication. The discourse allows the legitimacy or the resistance of an innovation by constructing congruence or incongruence among institutional logics, then, it can be seen as a facilitator of the diffusion of institutional logics. The discursive process goes beyond the simply speech. It includes the interactive processes by which ideas are conveyed, the message, the context and the actors involved, that is, the whole discursive structure. In this context, one of the discourses that have gained notoriety is the discourse of humanization, by which government actions and women's organized groups defend the rescue of natural childbirth and maternity, which were once dominant. One of these groups that stands out in the city of Maringa - PR is Maternati, Group of Pregnant Women and Mothers. In view of this, this research aims to comprehend how the discursive structure predominant in Maternati, in the period of 2014 to 2015, intervened in the resumption of the natural logics of maternity. Regarding to the methodological procedures, this research is characterized as qualitative, descriptive and sectional with longitudinal evaluation, having as methodological strategy the case study. Data were collected through documental research, interviews and non-participant observation, and they were analyzed through the critical discourse analysis. The results showed that the institutional logics of maternity had been presented as historically contingent, and it had been identified two types of change: the replacement and the resumption. The resumption can be characterized as a search for naturalization, which adopts the former natural maternity logics as a reference, but situate and adapt it to the new actors and contexts. Furthermore, it was possible to conclude that the group's discursive structure has facilitated the resumption of the maternity logics and its institutionalization through four main aspects: group identification, system construction, environmental construction, and recursive movement. Therefore, it is concluded that the use of discourse has operated as an essential mechanism so that inherent contradictions in interdependent institutional orders could be legitimized and then caused change processes in institutional logics. The resumption of natural maternity logic has been enabled through the perception of change as coherent by the members of the group, which has been connected to the actors? identifications. These identifications have occurred through shared discourses which, as been conveyed among the group, made it possible to recursively characterize and distinguish the system and its environment, providing a convincing scenario of change.